The mTOR Deficiency in Monocytic Myeloid-Derived Suppressor Cells Protects Mouse Cardiac Allografts by Inducing Allograft Tolerance - Li, Jiawei; Chen, Juntao; Zhang, Mingnan; Zhang, Chao; Wu, Renyan; Yang, Tianying; Qiu, Yue; Liu, Jingjing; Zhu, Tongyu; Zhang, Yi; Rong, Ruiming (Frontiers in Immunology, 2021)
Background Myeloid-derived suppressor cells (MDSCs) can prevent allograft rejection and induce immune tolerance in transplantation models. Previous studies have demonstrated that inhibition of mTOR signaling can enhance the MDSC protective effect in heart transplantation (HTx) by promoting MDSC expansion. In addition, mTOR inhibition is related to autophagy. The present study investigated the protective mechanism of mTOR-deficient monocytic MDSCs (M-MDSCs) in mouse HTx. Methods Myeloid-specific mTOR conditional knockout mice were generated to obtain mTOR−/− M-MDSCs. The proliferation and immunosuppressive function of mTOR−/− M-MDSCs were determined by flow cytometry and T cell proliferation assays. The mTOR−/− M-MDSC intracellular autophagy levels were determined using western blotting and electron microscopy. RNAseq analysis was performed for wild-type (WT) and mTOR−/− M-MDSCs. Allogeneic HTx mouse model was established and treated with WT or mTOR−/− M-MDSCs. Enzyme-linked immunosorbent assay, flow cytometry, and immunohistochemistry assays were performed to determine WT and mTOR−/− M-MDSC-induced immune tolerance. Results The mTOR deficiency promoted M-MDSC differentiation and enhanced intracellular autophagy levels in vivo and in vitro. mTOR deficiency also enhanced the immunosuppressive function of M-MDSCs. In addition, infusing with WT and mTOR−/− M-MDSCs prolonged cardiac allograft survival and established immune tolerance in recipient mice by inhibiting T cell activation and inducing regulatory T cells. Conclusion mTOR deficiency enhances the immunosuppressive function of M-MDSCs and prolongs mouse cardiac allograft survival.